Oscillating-wing unit for power generation. (June 2019) - Liu, Tianshu; Ramasamy, RS Vewen; Radermacher, Ryne; Liou, William; Salazar, David Moussa
This paper describes an exploratory study of a nonconventional wind power converter with a pair of oscillating wings, which is called an oscillating-wing unit. The working principles of the oscillating-wing unit are described, including the aerodynamic models, kinematical, and dynamical models. The performance of the oscillating-wing unit is evaluated through computational simulations and the power scaling in comparison with conventional horizontal-axis wind turbines. Then, a model oscillating-wing unit is designed, built, and tested in a wind tunnel to examine the feasibility of the oscillating-wing unit in extraction of the wind energy in comparison with the theoretical analysis. The theoretical analysis and experimental data indicate that the oscillating-wing unit has the power efficiency comparable to the conventional horizontal axis wind turbine and it can operate at low wind speeds.